Physical Activity Participation of Persons Deprived of Liberty in Santiago City District Jail, Philippines - Niño Nadera Baldonado; Ana Maria Libao Demot; Peter John Aguinaldo Villaflores; Geneviv Gumpal Dayag; Esperanza Leonidas Buado; Christian Velasco Ramos; Gil Vincent Tiaño Dela Cruz; Rhealyn Galaus Martinez (Physical Education and Sports: Studies and Research, 2022)
Background: Physical activity in prison systems worldwide has been ignored for decades. The congested status of penal institutions around the country tends to breed unhealthy living conditions. Also, they are often deprived of physical activities due to limited opportunities. A person deprived of liberty means a person who has been arrested, held in lawful custody, detained, or imprisoned in execution of a lawful sentence. Objectives: This study aims to determine the physical activities and the scale of physical activity satisfaction of persons deprived of liberty in Santiago City District Jail, Philippines. Methods: This descriptive study utilized a survey of 140 randomly selected detainees and face-to-face interviews with 30 randomly chosen detainees. The questionnaire is divided into three parts: respondents' profiles, physical activities, and the scale of physical activity satisfaction. The interview method validated the results of the survey. Jacob G. Beard and Mounir G. Ragheb developed the Physical Activity Satisfaction Scale. It was adopted, validated, and used to determine the inmates' physical activity level of satisfaction.  Results: Findings show that most of the inmate-respondents are generally engaged in games or sports, dance, and other livelihood activities on an irregular basis. They also pronounced their satisfaction with their physical activities as they benefited from physiological, relaxational, educational, psychological, social, and aesthetic domains. Conclusion: It can be concluded that games and sports activities are moderately and positively related to physical activities' psychological and relaxational domains of the inmates.